Numerical Investigations of Bond-Slip Performance in Pull-Out High Strength Concrete Specimens Subjected to Elevated - Mahmoud, Akram S.; Ahmed, Shamil K. (Anbar Journal of Engineering Sciences, 2021)
The concrete members several blessings over steel beam, like high resistance to prominent tem-perature, higher resistance to fatigue and buckling, high resistance to thermal shock, fire re-sistance, robust resistance against, and explosion. However there are some disadvantages as a result of exploitation totally different materials to product it. The most downside of structural concrete member is its deprived the strength to tensile stresses.The bond mechanism between steel bars and concrete is thought to be influenced by multiple parameters, like the strength of the encompassing media, the prevalence of cacophonous cracks within the concrete and therefore the yield stress of the reinforcement. However, properties of concrete mass has significantly effect when it was subjected to elevated temperature.The objective of this paper presents the results that allocating with the bond behavior of the rein-forcement of steel bar systems below static pull-out loading tests subjected to elevated tempera-tures. This numerical technique relies on relative slip and therefore the stress of bond distribu-tions done the embedded length and size of the bar within the concrete cylinder specimens. The obtained results square measure given and commented with the elemental characteristics of ferroconcrete members. The comparison showed smart agreement with experimental results